1978
DOI: 10.1016/s0022-5347(17)57082-2
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Metastatic Renal Cell Carcinoma: A Computer Analysis

Abstract: Survival factors of 86 patients with metastatic renal cell carcinoma were studied by computer analysis. Cumulative survival was 53 per cent at 6 months, 43 per cent at 1 year, 26 per cent at 2 years and 13 per cent at 5 years. Survival was influenced favorably by confinement of metastases to the lungs, by the absence of local recurrence or persistence of tumor and by a longer interval free of disease after removal of the primary tumor. Medical therapy improved survival during the first year after diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
148
0
29

Year Published

1980
1980
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 495 publications
(180 citation statements)
references
References 9 publications
3
148
0
29
Order By: Relevance
“…Since the incidence of regression of metastases had been less than 1%, Middleton [20] calculated that the morbidity and mortality from nephrectomy in these patients are higher than the potential benefit and therefore concluded that nephrectomy for the sole purpose of achieving regression of metastases is not warranted in asymptomatic patients. The rnortality of adjunctive nephrectomy under these circumstances ranges from 2 to 15%; most of the authors report 5% [6,22,25].…”
Section: Discussionmentioning
confidence: 99%
“…Since the incidence of regression of metastases had been less than 1%, Middleton [20] calculated that the morbidity and mortality from nephrectomy in these patients are higher than the potential benefit and therefore concluded that nephrectomy for the sole purpose of achieving regression of metastases is not warranted in asymptomatic patients. The rnortality of adjunctive nephrectomy under these circumstances ranges from 2 to 15%; most of the authors report 5% [6,22,25].…”
Section: Discussionmentioning
confidence: 99%
“…14 Metastatic disease is seen in 25-40% of the cases at diagnosis, 15,16 with a 5-year survival rate of 13%. 17 Twenty years ago, the incidental case rate was less than 5%, but there has been an increase of more than 50% in early diagnosis up to the present day, due to the advent of non-invasive radiological techniques such as ultrasonography and computerized tomography (CT) scans. This has allowed small lesions with favorable prognosis and low incidence of metastasis to be discovered.…”
Section: Introductionmentioning
confidence: 99%
“…3 Furthermore, survival 3 years after the beginning of treatment is between 19% and 31%, 24 -29 5-18% being the survival of non-treated patients (Table VIII). 30,31 Sporadic long-term survivors are observed only among patients who underwent complete remission. 29,32 In the past 14 years, we have treated 122 MRCC patients with intralymphatic injection of non-recombinant IL-2, LAK cells, IFN and TF.…”
Section: Discussionmentioning
confidence: 99%